Step
*
1
2
of Lemma
bag-combine-com
1. A : Type
2. B : Type
3. C : Type
4. f : A ⟶ B ⟶ bag(C)
5. ba : bag(A)
6. as : B List
7. bs : B List
8. permutation(B;as;bs)
⊢ ⋃b∈as.⋃a∈ba.f[a;b] = ⋃b∈bs.⋃a∈ba.f[a;b] ∈ bag(C)
BY
{ ((Assert (as = bs ∈ bag(B)) ∧ (as ∈ bag(B)) ∧ (bs ∈ bag(B)) BY Auto)⋅ THEN Auto THEN EqCD THEN Auto)⋅ }
Latex:
Latex:
1.  A  :  Type
2.  B  :  Type
3.  C  :  Type
4.  f  :  A  {}\mrightarrow{}  B  {}\mrightarrow{}  bag(C)
5.  ba  :  bag(A)
6.  as  :  B  List
7.  bs  :  B  List
8.  permutation(B;as;bs)
\mvdash{}  \mcup{}b\mmember{}as.\mcup{}a\mmember{}ba.f[a;b]  =  \mcup{}b\mmember{}bs.\mcup{}a\mmember{}ba.f[a;b]
By
Latex:
((Assert  (as  =  bs)  \mwedge{}  (as  \mmember{}  bag(B))  \mwedge{}  (bs  \mmember{}  bag(B))  BY  Auto)\mcdot{}  THEN  Auto  THEN  EqCD  THEN  Auto)\mcdot{}
Home
Index